Processing and classification methods of UAV photogrammetric point clouds for forest structure and fire behaviour analysis - Juan Pedro Carbonell-Rivera; Luis Ángel Ruiz Fernández; Javier Estornell Cremades (Revista de Teledetección)
Tesis doctoral: